CASE STUDY : IMPLEMENTATION OF PHYSIOTHERAPY FOR DELAYEDDEVELOPMENT WITH NEURO SENSORY REFLEX DEVELOPMENT &SYNCHRONIZATION (NSMRD&S), NEURO DEVELOPMENT TREATMENT(NDT), AND PLAY EXERCISE MODALITIES - Nasywa Aqiila; Nur Susanti (SINERGI : Jurnal Riset Ilmiah, 2026)
Background: Delayed Development (DD) is a form of developmental delay characterized by motor skill deficits relative to peers; it can affect sensory function, reflexes, muscle strength, functional abilities, and overall growth and development. The prevalence of DD at YPAC Surakarta rose from 116 patients in 2017 to 135 patients in 2018, highlighting the need for appropriate physiotherapy management. Objective: To determine the effectiveness of physiotherapy using NSMRD & S, NDT, and Play Exercise on improvements in sensory function, reflexes, muscle strength, functional ability, and child growth and development. The study employed a descriptive-analytic method using a case study design; assessments utilized sensory and reflex checklists, XOTR, GMFM, and DDST, and the intervention consisted of six therapy sessions. Results: An improvement in personal-social and fine motor development was observed, rising from 62.5% to 87.5% after six therapy sessions. Conclusion: NSMRD & S, NDT, and Play Exercise can reduce problems in Delayed Development (DD). Parents are encouraged to continue regular exercise and stimulation at home to maintain and optimize therapy results.